Oil Refining: Yield Coefficients and Actual Prices - Manne, Allan S. (Quarterly Journal of Economics, 1951)
I. Introduction, 400. — II. Cracking yield coefl&cients: general approach, 401. — III. Yield data: individual processes, 404. — IV. Yield coefficients and actual prices, 408. — V. Conclusions, 415.